Effects of Ni addition on mechanical properties and corrosion behaviors of coarse-grained WC-10(Co, Ni) cemented carbides. (April 2019) - Zhang, Xiang; Zhou, Jianhua; Liu, Chao; Li, Kun; Shen, Weijun; Lin, Zhao; Li, Zhifeng; He, Yuehui; Lin, Nan
Abstract: The effects of the Ni content on the mechanical properties and corrosion behavior of coarse-grained WC-10Co cemented carbide, with a grain size of 3.5 μm, were investigated using scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), electrochemical measurements, and mechanical property tests. The results indicate that the strength and toughness are improved with the addition of 2 wt% Ni without sacrificing hardness. Furthermore, the existence of Ni can decrease the corrosion current density (icorr ) of WC-10Co cemented carbide in both 0.1 M HCl and 0.1 M NaOH solutions. The SEM and XPS results reveal that only a minor amount of WO3 formed in the corroded surface in HCl solution. The corrosion behavior was determined by the dissolution of the binder phase, and Ni can develop the charge-change resistance (Rct ). Contrarily, the Co binder phase were oxidized to a dense passive film (Co(OH)2 and Co3 O4 ) in NaOH solution, and the addition of Ni was conducive to the enhancement of the diffusion resistance (Rf ). This may give insights into adding an appropriate Ni content in coarse-grained WC-Co cemented carbide, in which the wear and corrosion of the components coexist. Highlights: Ni can promote the growth of WC grain and the formation of more (001) plane for the coarse grained WC-Co cemented carbide. WC-10Co cemented carbide containing Ni exhibited the better corrosion resistant than straight WC-10Co cemented carbide in both acidic and alkaline solutions. Adding an appropriate Ni content in coarse grained WC-Co cemented carbide is promising method for applications where wear and corrosion of components co-exist.